2019
DOI: 10.1002/14651858.cd012741.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic cyclophotocoagulation (ECP) for open angle glaucoma and primary angle closure

Abstract: Endoscopic cyclophotocoagulation (ECP) for open angle glaucoma and primary angle closure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 29 publications
0
16
0
1
Order By: Relevance
“…We included trials in which CPC was performed alone or in combination with another procedure. We excluded trials in which endoscopic cyclophotocoagulation was compared with non-cyclodestructive glaucoma treatments, as these trials are covered in another Cochrane Review (Tóth 2017). …”
Section: Methodsmentioning
confidence: 99%
“…We included trials in which CPC was performed alone or in combination with another procedure. We excluded trials in which endoscopic cyclophotocoagulation was compared with non-cyclodestructive glaucoma treatments, as these trials are covered in another Cochrane Review (Tóth 2017). …”
Section: Methodsmentioning
confidence: 99%
“…640 Another 2019 Cochrane Systematic Review identified no studies on the effects of endocyclophotocoagulation for open-angle glaucoma. 641 Additional randomized clinical trials are needed to further elucidate the merits of each type of cyclophotocoagulation relative to one another as well as to other types of glaucoma surgery. 640,641 Therefore, the selection of cyclophotocoagulation over other procedures should be left to the discretion of the treating ophthalmologist, in consultation with the individual patient.…”
Section: P112mentioning
confidence: 99%
“…There is, however, limited knowledge of the safety profile of ECP due to the lack of high-level evidence in the form of randomised controlled trials. One study, currently in the data collection phase, is investigating patients with POAG receiving either ECP with phacoemulsification or phacoemulsification as a standalone procedure [28] .…”
Section: Migs Targeting the Ciliary Processmentioning
confidence: 99%